Pola Pertanggungjawaban Rumah Sakit Dalam Penyelesaian Sengketa Medis Di Indonesia - Andrianto, Wahyu; Achmad Andaru, Djarot Dimas (UI Scholars Hub, 2019)
Several cases of medical disputes between patients and hospitals include the case of missing baby number 98 at Hasan Sadikin Hospital Bandung in 1987, the false gas case in which O2 Gas is exwith CO2 Gas during an operation at the RSUD M Yunus Bengkulu Hospital in 2001, and the Debora Case at the Hospital The Kalideres Jakarta Family Partner in 2017 — invited various questions about how the hospital as an institution of health service facilities, in this case, is responsible. In the 1945 Constitution Article 34 paragraph 3 explains that citizens have the right to receive proper welfare services, besides Article 1 paragraph 3 of the 1945 Constitution also confirms that the state of Indonesia is a state of law, meaning that all state administration including hospital health services must be based to the law. The pattern of government and hospital responsibility is regulated in the Civil Code (especially Article 1367 of the Civil Code) and the Hospital Law (specifically Article 46).